Interactive Shopping Behavior and Its Influence on Consumer Purchasing Decisions: A Systematic Literature Review - Yusak Taufan (Jurnal Ekuisci, 2026)
Background. The shift in the global market paradigm from a conventional one-way transaction model to a highly dynamic digital ecosystem has forced business organizations to re-evaluate their brand messaging delivery mechanisms. Aims. This study aims to deconstruct the dynamics of interactive shopping behavior on consumer purchasing decisions in the era of digital transformation. Methods. Through the Systematic Literature Review (SLR) method that adopts the PRISMA protocol, as many as 35 articles from reputable international journals in the range of 2020-2026 were identified, extracted, and synthesized thematically. Result. The results show that the latest shopping technologies (such as live-streaming, AI marketing, and Augmented Reality) have been shown to speed up the transaction cycle by mitigating the functional risks of pre-purchases, although their effectiveness remains dependent on the platform's trust factor. Furthermore, in processing online review information, consumer cognition is governed by the negativity bias, whereby negative reviews from fellow consumers are processed faster and trigger greater cognitive conflict than positive reviews from experts. This research also reveals the existence of an attitude-behavior gap (green gap), where consumers' intention to buy green products or healthy foods is often canceled due to premium price barriers, mental burdens, and daily mental fatigue at the retail level. Conclusion. In conclusion, the purchasing decisions of contemporary consumers are no longer linear but rather a non-linear estuary of convergence among the axes of platform sophistication, the validity of social information signals, and economic compromise calculations. Implementation. This research makes a theoretical contribution in reconceptualizing conventional consumer behavior theory and provides practical guidance for the industry to mitigate reputational risks through a solution-oriented post-purchase operational policy.